2014
DOI: 10.1371/journal.pone.0103478
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor-5 Deficiency Ameliorates Disease Severity in the MRL/lpr Mouse Model of Lupus in the Absence of a Mutation in DOCK2

Abstract: Interferon regulatory factor 5 (IRF5) polymorphisms are strongly associated with an increased risk of developing the autoimmune disease systemic lupus erythematosus. In mouse lupus models, IRF5-deficiency was shown to reduce disease severity consistent with an important role for IRF5 in disease pathogenesis. However these mouse studies were confounded by the recent demonstration that the IRF5 knockout mouse line contained a loss-of-function mutation in the dedicator of cytokinesis 2 (DOCK2) gene. As DOCK2 regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…This led to conflicting results within the field, including data regarding Type I IFN and antibody production (152), and led to the necessity for rederivation of many Irf5 -/-colonies in order to gain confidence in observed phenotypes -particularly those associated with B-cells. Of note, the observations described for IRF5 in the MRL/lpr model of SLE have been verified as independent of Dock2 mutations (153). Irf5 -/-mouse colonies should therefore now be routinely screened for Dock2 mutations.…”
Section: To Suppression Of Mucosal T H 1/t H 17 Responses In Chronic mentioning
confidence: 80%
“…This led to conflicting results within the field, including data regarding Type I IFN and antibody production (152), and led to the necessity for rederivation of many Irf5 -/-colonies in order to gain confidence in observed phenotypes -particularly those associated with B-cells. Of note, the observations described for IRF5 in the MRL/lpr model of SLE have been verified as independent of Dock2 mutations (153). Irf5 -/-mouse colonies should therefore now be routinely screened for Dock2 mutations.…”
Section: To Suppression Of Mucosal T H 1/t H 17 Responses In Chronic mentioning
confidence: 80%
“…We hypothesized that IRF5 deficiency would reduce atherosclerosis severity in the context of lupus for two main reasons. Firstly, the inflammation due to the active autoimmune process is thought to contribute to the premature atherosclerosis in SLE (2) and previous studies in other lupus mouse models suggested that IRF5 deficiency would reduce the active autoimmune process (27-32). Secondly, atherosclerosis itself, independently of systemic autoimmune disease, is driven by a Th1-skewed chronic inflammatory process in which M1-type macrophages play a dominant role (11), and IRF5 has been shown to promote both Th1 responses and M1-type macrophage development (25, 26).…”
Section: Discussionmentioning
confidence: 99%
“…IRF5 promotes T helper 1 (Th1)/Th17-type immune responses and LPS-induced M1 macrophage polarization (25, 26). IRF5 deficiency ameliorates disease in a number of murine lupus models (27-32). For these reasons, IRF5 is being considered as a potential therapeutic target in SLE and other autoimmune diseases as well as in other inflammatory conditions such as post-myocardial infarction healing (14, 33).…”
Section: Introductionmentioning
confidence: 99%
“…Interferon regulatory factor 5 (IRF-5) is a member of the IRF family of transcription factors that induces the expression of type I IFN and IFN-inducible genes [ 28 30 ]. In IRF5 −/− MRL/lpr mice, IFN α and autoantibody production were markedly reduced, and glomerulonephritis was much improved [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%